A preliminary review of Nephelomys albigularis (Tomes, 1860) (Rodentia: Cricetidae), with the description of a new species from the Peruvian montane forests - Ruelas, Dennisse; Pacheco, Víctor; Inche, Betsy; Tinoco, Nicolas (Zootaxa, 2021)
Nephelomys albigularis is a sigmodontine rodent of the tribe Oryzomyini distributed in the Andean forests from central Ecuador to central Peru. Although several studies recognize this species as monotypic, significant morphological variation has been reported in Peruvian populations that were not properly assessed by direct comparisons with the type series from central Ecuador. We present a preliminary review of N. albigularis with an integrative approach and emphasis on Peruvian populations. We analyzed specimens using morphological and morphometric methods, complemented with phylogenetic analyses and species delimitation using sequence data from the cytochrome-b gene. Our results reveal that N. albigularis (sensu lato) comprises two taxa: N. albigularis s.s., from the montane forests in central and southern Ecuador and northwestern Peru, and Nephelomys sp. nov. from montane forest east of the Marañón River. These taxa are morphologically distinct and are separated by a genetic distance of 5.90 ± 1.01%. Nephelomys sp. nov. differs from N. albigularis s.s. by longer rump hairs, narrow hypothenar pads, faintly bicolor tail; absent interorbital ridges, low zygomatic plates, smoothly squared posterior margin of the hard palate or with a small median postpalatal process, smoothly edged ventral margin of the external auditory meatus, and slightly angular mandibular sigmoid notches. In this work, we present a diagnosis and description of the new species of Nephelomys and discuss the role of the Marañón River as a potential driver for speciation in the genus Nephelomys.